PORTABILITY OF GWAS RESULTS BETWEEN ETHNIC POPULATIONS: GENETIC MARKERS FOR POLYCYSTIC OVARY SYNDROME (PCOS) IN MEDITERRANEAN AREA - Douma, Z. (Acta Endocrinol (Buchar), 2019)
Genome Wide Association Studies (GWAS) are excellent opportunities to define culprit genes in complex disorders such as the polycystic ovary syndrome (PCOS). PCOS is a prevalent disorder characterized by anovulation, hyperandrogenism and polycystic ovaries, which benefitted from several GWASs in Asians and Europeans revealing more than 20 potential culprit genes near associated single nucleotide variations (SNV). Translation of these findings into the clinical practice raises difficulties since positive hits are surrogate SNVs linked with causative mutations by linkage disequilibrium (LD). Studies in Mediterranean populations (e.g. Southern Europe and North Africa) raise supplementary problems because of a different LD-pattern, which may disrupt the link with causative mutations. Our experience in MEDIGENE program between Tunisia and France enforces the necessity of genetic anthropology studies before translating GWAS data. Tunisians are a heterogeneous population with ancestral Berbers, European, Arab and Sub-Saharan African components while South Europeans display a high level of genetic diversity, partially explained by gene flow from North Africa. Human diversity studies require sampling from Middle East and North Africa (MENA) region that will help to understand genetic factors in complex diseases.